2021
DOI: 10.1186/s43019-021-00116-0
|View full text |Cite
|
Sign up to set email alerts
|

Open reduction and internal fixation using multiple nonabsorbable suture materials in acute patella fracture: comparison of clinical and radiological outcome with tension band wiring

Abstract: Background For treating displaced patella fractures, tension band wiring is the most widely used technique. However, implant removal surgery is often necessary to alleviate discomfort caused by fixation materials. On the contrary, fixation using nonabsorbable suture materials is anticipated to result in comparable outcomes without need for further implant removal surgery. However, there is a lack of clinical studies comparing the two fixation techniques (wire and nonabsorbable suture materials)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
6
1
Order By: Relevance
“…Greenberg et al suggested that removal gives significant pain relief but doesn’t significantly improve the functional limitations [ 19 ]. We observed an overall rate of removal to be 20.5% (one in five cases) which is lower when compared to other published literature reporting removal rates at 17% to 70% [ 3 , 8 , 12 , 17 , 19 - 21 ]. The left or right side had no relation to removal rates (equivocal).…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…Greenberg et al suggested that removal gives significant pain relief but doesn’t significantly improve the functional limitations [ 19 ]. We observed an overall rate of removal to be 20.5% (one in five cases) which is lower when compared to other published literature reporting removal rates at 17% to 70% [ 3 , 8 , 12 , 17 , 19 - 21 ]. The left or right side had no relation to removal rates (equivocal).…”
Section: Discussioncontrasting
confidence: 82%
“…Patella plays a pivotal role in maintaining the integrity of the knee extensor mechanism acting as a fulcrum of the lever of the quadriceps. Thus, any disruption needs intervention to help the patient regain knee extension and independent mobilization [ 11 , 12 ]. A conservative approach is often followed only if there is no articular step, the fracture is undisplaced or the patient is not fit for surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Owing to these multifragmentary fracture patterns and inherent weak small bone in distal fragments, the tension band wiring technique is not feasible because it requires an intact cortical buttress to withstand compression and firm fixation to withstand the tensile forces. 32–35 Therefore, alternative fixation modalities are needed for secure fixation. Two main available options are partial patellectomy or reattachment of the distal fragment using various methods.…”
Section: Discussionmentioning
confidence: 99%
“…TBW is the traditional surgical method for treating patellar fractures. In particular, transverse fractures with large fragments can be easily reduced to obtain and maintain fracture fixation using TBW [ 7 ]. However, TBW is often insufficient to achieve rigid fixation due to comminuted and small fracture fragments in comminuted inferior pole fractures [ 8 ].…”
Section: Introductionmentioning
confidence: 99%